Eco-friendly mining in the Himalaya: a case study of Kharidhunga magnesite deposit, Nepal (Journal of Nepal Geological Society, 1998)
Mining is one of the core sector industries which plays a positive and significant role in the process of country's economic development causing some unavoidable environmental impacts. Environment has become a key issue and today have transgressed the national boundaries and have now become a part of the global concern. We need eco-friendly mining for sustained development and better quality of life with minimum negative impact on environment without any threat to the future generation. In short, a balance has to be struck between development, environment and mining. Nepal has very short history of commercial mining and existing mines are small in size, located in hilly terrain and are being mined by opencast method. The mining activities may cause serious environmental degradation if proper techniques, management policies and practices are not utilised in time. This paper presents the holistic environment promotional effects which have been introduced at Kharidhunga magnesite mine.